2008
DOI: 10.3724/sp.j.1141.2008.00297
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition and Diversity of Fish Larvae and Juveniles in the Surf Zone of the Yangtze River Estuary

Abstract: Zoological Research 长江口沿岸碎波带仔稚鱼的种类组成及其多样性特征Abstract: This study investigated species composition and diversity of fish larvae and juveniles in the surf zone of the Yangtze River estuary to reveal the importance of this habitat as a fish nursery ground. Fish larvae and juveniles were collected monthly at 13 stations on the spring tide during July 2006 and June 2007. Samples were conducted along the surf zone (depth of 0.5-1.5 m) using a seine net (1 m×4 m, 1 mm mesh-aperture). Each haul was made parallel to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Multiple measures have been applied to mitigate the negative effects of environmental changes on fish resources in the Yangtze Estuary, such as closed fishing seasons, chartered fishing on typical populations, and establishing of nature reserves (Zhuang et al 2006). However, declines of fish resources in the estuary have not subsided (Zhuang et al 2006;Jiang et al 2009). Patterns of larval fish assemblages reflect the spawning and nursery functions of an estuary for fish (Strydom 2015;Teodosio and Garel 2015;Jiang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple measures have been applied to mitigate the negative effects of environmental changes on fish resources in the Yangtze Estuary, such as closed fishing seasons, chartered fishing on typical populations, and establishing of nature reserves (Zhuang et al 2006). However, declines of fish resources in the estuary have not subsided (Zhuang et al 2006;Jiang et al 2009). Patterns of larval fish assemblages reflect the spawning and nursery functions of an estuary for fish (Strydom 2015;Teodosio and Garel 2015;Jiang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on larval fish assemblages in the Yangtze Estuary have focused mainly on areas outside of the mouth (Liu et al 2008;Liu and Xian 2009;Jiang et al 2016). Detailed information covering the larval fish assemblage inside of the mouth is limited, with few exceptions describing the distribution of larvae and juveniles in the surf zones (Zhong et al 2005;Jiang et al 2009). In this study, we investigated larval fish assemblages and environmental factors monthly throughout a year across three sections within the SBYE.…”
Section: Introductionmentioning
confidence: 99%
“…There was also some research conducted regarding both abundance and assemblage structure of larval fish in the estuary (Zhong et al, 2005;Jiang et al, 2010). However, until this study, there has been no research into the spatial and temporal patterns of larval fish in the lower reach.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have reported adverse effects of the Three Gorges Dam on populations of these four species (Li et al, 2011;Song et al, 2017). Other studies have focused on the distribution and assemblage structure of larval fish, although these surveys have mainly been conducted in the estuary (Jiang, Zhong & Zhou, 2010;Gao et al, 2018) and tributaries of the upper reaches of the Yangtze River (Liu et al, 2014;Wang H. et al, 2017). However, research on the early life stages of fishes is rare in the lower reach of the Yangtze River, with the exception of our previous study, which investigated monthly occurrences of larval fish, described the annual composition of larval assemblages, identified the prevailing fish spawning season (mid-April to mid-August), and implied potential influences of landscape patterns in the lower reaches (Ren et al, 2016).…”
Section: Introductionmentioning
confidence: 99%